2019
DOI: 10.1111/jan.13963
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ decision‐making, practices and perceptions of patient involvement in medication administration in an acute hospital setting

Abstract: Aims To describe nurses’ decision‐making, practices and perceptions of patient involvement in medication administration in acute hospital settings. Background Medication errors cause unintended harm to patients. Nurses have a major role in ensuring patient safety in medication administration practices in hospital settings. Investigating nurses’ medication administration decision‐making and practices and their perceptions of patient involvement, may assist in developing interventions by revealing how and when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…This research was mainly conducted in Europe (n = 26) (34, 37, 39–43, 45, 46, 48–50, 52, 55, 57, 62, 63, 65–72, 74); 69% (n = 18) of the European studies were conducted in Sweden (34, 37, 39, 41, 42, 45, 46, 48, 49, 52, 55, 57, 66, 67, 69–72). The remaining studies were conducted in Australia (n = 8) (47, 51, 54, 58–60, 64, 75), North America (n = 5) (33, 38, 53, 61, 76), Asia (n = 3) (44, 73, 77) and the United Kingdom (n = 1) (56) (See Table 3). Samples consisted of patients (n = 17) (41, 45–47, 49, 51, 53, 55, 56, 61, 62, 64, 65, 67–69, 76), nurses (n = 15) (33, 34, 37, 39, 40, 43, 50, 52, 57, 60, 70–73, 75), or patients and nurses (n = 11) (38, 42, 44, 48, 54, 58, 59, 63, 66, 74, 77), and an ‘a theoretical’ approach was undertaken in 86% (n = 37) of studies (33, 34, 37–48, 51, 53–61, 63, 64, 66, 67, 69–77).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This research was mainly conducted in Europe (n = 26) (34, 37, 39–43, 45, 46, 48–50, 52, 55, 57, 62, 63, 65–72, 74); 69% (n = 18) of the European studies were conducted in Sweden (34, 37, 39, 41, 42, 45, 46, 48, 49, 52, 55, 57, 66, 67, 69–72). The remaining studies were conducted in Australia (n = 8) (47, 51, 54, 58–60, 64, 75), North America (n = 5) (33, 38, 53, 61, 76), Asia (n = 3) (44, 73, 77) and the United Kingdom (n = 1) (56) (See Table 3). Samples consisted of patients (n = 17) (41, 45–47, 49, 51, 53, 55, 56, 61, 62, 64, 65, 67–69, 76), nurses (n = 15) (33, 34, 37, 39, 40, 43, 50, 52, 57, 60, 70–73, 75), or patients and nurses (n = 11) (38, 42, 44, 48, 54, 58, 59, 63, 66, 74, 77), and an ‘a theoretical’ approach was undertaken in 86% (n = 37) of studies (33, 34, 37–48, 51, 53–61, 63, 64, 66, 67, 69–77).…”
Section: Resultsmentioning
confidence: 99%
“…Both interventional and noninterventional research studies were retrieved. Thirty‐three studies were noninterventional (33, 34, 37, 39–44, 46, 48, 50–52, 54, 56–65, 68–71, 73, 75–77). The focus of most noninterventional research was exploring patient and/or nurses perceptions’/experiences’ of general patient participation/engagement/empowerment/involvement processes (n = 14) (33, 34, 37, 39–41, 44, 46, 50, 56, 57, 62, 70, 76).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although studies often cite the patient and family as contributing to distractions, there is little research into the potential advantage of forming a partnership between the patient/family and nurse to improve medication safety (Wimpenny & Kirkpatrick, ). Several nurses in this study identified the potential safety ramifications of pursuing greater patient–nurse collaboration around HAM safety, a topic that merits further research (Bucknall et al, ).…”
Section: Discussionmentioning
confidence: 99%